2019
DOI: 10.1177/0956797619848351
|View full text |Cite
|
Sign up to set email alerts
|

The Grateful Don’t Cheat: Gratitude as a Fount of Virtue

Abstract: Gratitude has been linked to behaviors involving the exchange of resources; it motivates people to repay debts to benefactors. However, given its links to self-control—itself a necessary factor for repaying debts—the possibility arises that gratitude might enhance other virtues unrelated to exchange that depend on an ability to resist temptation. Here, we examined gratitude’s ability to function as a “parent” virtue by focusing on its ability to reduce cheating. Using real-time behavior-based measures of cheat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 16 publications
2
13
0
1
Order By: Relevance
“…In most gratitude studies that we are aware of, either no instruction was given, or in the case of prosocial studies, a request was given to secure the grateful participants' help. For instance, in Tsang (2006), participants were not instructed on how they should distribute monetary rewards, and in Tong andYang (2011) andDeSteno et al (2019), participants were not given any instruction on how they should respond in a task that offered an opportunity to cheat anonymously. In Bartlett and DeSteno (2006), participants were politely requested to fill up a taxing survey.…”
Section: Discussionmentioning
confidence: 99%
“…In most gratitude studies that we are aware of, either no instruction was given, or in the case of prosocial studies, a request was given to secure the grateful participants' help. For instance, in Tsang (2006), participants were not instructed on how they should distribute monetary rewards, and in Tong andYang (2011) andDeSteno et al (2019), participants were not given any instruction on how they should respond in a task that offered an opportunity to cheat anonymously. In Bartlett and DeSteno (2006), participants were politely requested to fill up a taxing survey.…”
Section: Discussionmentioning
confidence: 99%
“…A 2014 study led by De Steno found that self-control increased significantly when participants felt emotions of gratitude. [15] Self-control helps people to be more focused and can lead to long-term happiness.…”
Section: Daily Gratitude Journalmentioning
confidence: 99%
“…Because emotions serve to inform the mind's predictions regarding adaptive behavior, we suspected that gratitude, given its links to increased cooperation and self-control (DeSteno, Li, Dickens, & Lerner, 2014;DeSteno, Duong, Lim, & Kates, 2019;DeSteno, Bartlett, Baumann, Williams, & Dickens, 2010;Smith, Pederson, Forster, McCullough, & Lieberman, 2017), might Gratitude and Resource Use 4 serve to combat the tendency to increase resource extraction in the face of other people's selfish behavior. That is, feelings of gratitude, even when incidental to the decision at hand, might nudge people toward decisions that, if widely enacted, would reduce the tendency to deplete publicly available resources.…”
Section: Gratitude and Resource Usementioning
confidence: 99%